2009
DOI: 10.1002/jcb.22309
|View full text |Cite
|
Sign up to set email alerts
|

Slug is a downstream mediator of transforming growth factor‐β1‐induced matrix metalloproteinase‐9 expression and invasion of oral cancer cells

Abstract: Members of Snail family of transcription factors play an important role in oral cancer progression by inducing epithelial-mesenchymal transition, by promoting invasion and by increasing matrix metalloproteinase (MMP) expression. Although Snail (Snai1) is the best characterized and the most extensively studied member of this family, the role and regulation of Slug (Snai2) in oral cancer progression is less well understood. In this report, we show that transforming growth factor-beta1 (TGF-beta1) increases Slug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 55 publications
(86 reference statements)
11
78
3
1
Order By: Relevance
“…Indeed, Slug overexpression is an indicator of poor overall survival in patients with lung cancer and, in agreement with our observations, Slug promotes invasion of lung cancer cells in vitro and in mouse models (13). Moreover, it was shown that Slug facilitates invasion of both pancreatic and oral cancer cells through upregulation of MMP-9 (24,25). In addition, Vuoriluoto and colleagues previously demonstrated that Slug induces vimentin expression and migration in mammary cells (26).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, Slug overexpression is an indicator of poor overall survival in patients with lung cancer and, in agreement with our observations, Slug promotes invasion of lung cancer cells in vitro and in mouse models (13). Moreover, it was shown that Slug facilitates invasion of both pancreatic and oral cancer cells through upregulation of MMP-9 (24,25). In addition, Vuoriluoto and colleagues previously demonstrated that Slug induces vimentin expression and migration in mammary cells (26).…”
Section: Discussionsupporting
confidence: 90%
“…It was recently reported that hundreds of proteins are under ERK-dependent control (20). Snai2 belongs to the Snail family of zinc-finger transcription factors, and is a well-established downstream target of the MAPK/ERK pathway in a number of cell types (21,22). Our previous study (23) demonstrated that the MAPK-Snai2 pathway played an important role in salivary adenoid cystic carcinoma (SACC) metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Snail family genes are also best known for their role in epithelial-to-mesenchymal transition (EMT) (24). In several types of human cancer, there is an inverse association between E-cadherin and Snail gene family expression (22,25,26). Wang et al (27) confirmed that Snai2 overexpression was correlated with reduced E-cadherin expression and enhanced vimentin expression in two independent cohorts of TSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of MT1-MMP-inducible OKF6 and SCC25 CellsThe coding sequence for the full-length MT1-MMP, the catalytically inactive EA, and the tail-deleted DC mutants of MT1-MMP have been described previously (30) and were subcloned into pRetroX-Tight-Pur vector (33). All plasmids were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%